O IMPACTO DA REDE DE APOIO NA ADESÃO AO ALEITAMENTO MATERNO NO PUERPÉRIO (REMUNOM, 2025)
Breastfeeding is an essential physiological process that brings benefits to both mother and baby, helping to strengthen the bond between them, improve the infant's immunity and have a positive impact on the breastfeeding woman's physical and mental health. However, factors such as the hormonal, physical and emotional changes of the puerperium, as well as adapting to a new routine, can make it difficult to continue breastfeeding, making it essential to have a support network. This network, made up of partners, family, friends and health professionals, plays a fundamental role in adhering to and maintaining breastfeeding, providing emotional and informational support to the mother. Research indicates that the active presence of a partner and family members, especially parents and grandparents, is associated with greater adherence to exclusive breastfeeding. However, the fragility of this network, marked by a lack of knowledge and the spread of beliefs and myths, can lead to the early interruption of breastfeeding. In order to reduce this problem, the work of health professionals is essential, promoting training and awareness among those involved. Despite the scientific evidence that proves the benefits of breastfeeding, the rate of exclusive breastfeeding in Brazil is still lower than expected, requiring the implementation of public policies and educational strategies to strengthen the support network and ensure better conditions for mothers. This study seeks to understand the impact of the support network on adherence to breastfeeding and to identify effective means of consolidating it.